Experimental Study of Forced Convection Heat Transfer Porous Media inside a Rectangular Duct at Entrance Region (Journal of University of Babylon for Engineering Sciences, 2019)
This work presents experimental investigation of flow and heat transfer characteristics for entry length of turbulent flow in a rectangular duct fitted with porous media and air as the working fluid. Rectangular duct (300×30 mm) with a hydraulic diameter (54.54 mm) was subjected to constant heat flux from lower surface (1.5 ×102 –1.8 ×102 w/m2) and Reynolds number ranged (3.3x104 up to 4.8x104). Copper mesh inserts (as porous media) with screen diameter (54.5 mm) for vary distance between two adjacent screens of (10 mm), (15 mm) and (20 mm) in the porosity range of (0.98 - 0.99) are considered for experimentation. The effect of porous height ratio (full and partial) are also considered. It is observed that the enhancement of heat transfer by using mesh inserts when compared to a plain surface is more by a factor of (2.2) times where the skin fraction coefficient is about (5) times. An Empirical correlation for Nusselt number and friction factor are developed for the mesh inserts from the obtained results.